The effectiveness of axial flow fans in a-frame plenums - Venter, Sarel Jacobus; Kroger, D. G. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Mechanical and Mechatronic Engineering)--University of Stellenbosch, 1990.